2018
DOI: 10.1002/mp.13247
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: U‐net‐generated synthetic CT images for magnetic resonance imaging‐only prostate intensity‐modulated radiation therapy treatment planning

Abstract: Purpose Clinical implementation of magnetic resonance imaging (MRI)‐only radiotherapy requires a method to derive synthetic CT image (S‐CT) for dose calculation. This study investigated the feasibility of building a deep convolutional neural network for MRI‐based S‐CT generation and evaluated the dosimetric accuracy on prostate IMRT planning. Methods A paired CT and T2‐weighted MR images were acquired from each of 51 prostate cancer patients. Fifteen pairs were randomly chosen as tested set and the remaining 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 34 publications
0
68
0
Order By: Relevance
“…Chen et al applied U-net to generate sCT images for MRI-only prostate intensity-modulated radiation therapy treatment planning. 52 They reported the MAE value within body outline was 29.96 AE 4.87 HU. The MAE from our proposed method was 54.2 HU for the brain data.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al applied U-net to generate sCT images for MRI-only prostate intensity-modulated radiation therapy treatment planning. 52 They reported the MAE value within body outline was 29.96 AE 4.87 HU. The MAE from our proposed method was 54.2 HU for the brain data.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Another attractive feature of deep learning techniques is that they can directly extract the relevant set of features from the data without requiring extensive feature engineering. As a result, recent papers have shown promising results from deep learning applied to sCT generation in brain [13][14][15][16][17][18] and pelvis 17,[19][20][21][22][23]…”
Section: Introductionmentioning
confidence: 99%
“…Han employed a pre‐trained U‐Net architecture to generate sCTs for brain tumor cases. Similarly, Fu et al and Chen et al generated sCTs of the male pelvis using 2D and 3D U‐Nets. Viewing the generation of sCTs from MR images as an image‐to‐image translation problem, Maspero et al implemented a generative adversarial network (GAN) named pix2pix that has demonstrated success in this space to produce sCTs for general pelvis cases.…”
Section: Introductionmentioning
confidence: 99%